PENINGKATAN HASIL BELAJAR MENULIS PUISI DENGAN MEDIA GAMBAR SERI PADA SISWA KELAS V SEKOLAH DASAR - Nurjani Nurjani (Ta'dib, 2020)
This research was conducted due to students’ difficulty in learning to write poetry, causing low learning outcomes. The purpose of this study is to describe the contribution of serial pictures within the stages of pre, whilst, and post-writing on poetry writing activities. This study was a Classroom Action Research applied in two cycles. The subject of the research was class IV students numbering 30 students. The research instruments were namely (1) observation, which was aimed at the teacher and students while conducting the learning process (2) interviews, several questions were posed to the teacher and students about the learning process, (3) tests, assessments given to students seeing the results of the treatment.  This research uses quantitative and qualitative data analysis. The results of the study describe, that the picture series media can build students' imagination, channel ideas, and motivate students in writing poetry, so that there is an increase in student learning outcomes from cycle I to cycle II, where student learning outcomes can meet predetermined graduation standards issued by the school. It concludes that student learning outcomes in writing poetry can be improved by the picture series media.